2011
DOI: 10.1037/a0025252
|View full text |Cite
|
Sign up to set email alerts
|

Expectation to receive methylphenidate enhances subjective arousal but not cognitive performance.

Abstract: Nonmedical use of prescription stimulant medication such as methylphenidate (MPH) has increased among college students over the past several years. Common motivations for use include enhancements in cognition and subjective arousal. As it is unclear whether stimulant medication exerts the same effect on healthy individuals as for those with ADHD, it is possible that many reported effects of prescription stimulants by healthy individuals may stem from placebo effects, which may be an important mechanism underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 44 publications
6
45
1
Order By: Relevance
“…Indeed, there is evidence that the belief that one receives active treatment sometimes predicts subjective responses better than the actual treatment [6]. Interestingly, the subjectively perceived improved concentration was not substantiated in better d2-R performance, which is in agreement with findings in healthy prescription stimulant-naive college students, who reported enhanced subjective arousal when assuming methylphenidate intake, while cognitive performance was in fact unchanged [7]. …”
Section: Figsupporting
confidence: 78%
“…Indeed, there is evidence that the belief that one receives active treatment sometimes predicts subjective responses better than the actual treatment [6]. Interestingly, the subjectively perceived improved concentration was not substantiated in better d2-R performance, which is in agreement with findings in healthy prescription stimulant-naive college students, who reported enhanced subjective arousal when assuming methylphenidate intake, while cognitive performance was in fact unchanged [7]. …”
Section: Figsupporting
confidence: 78%
“…Ilieva, et al, (2013) observed that individuals believed that their cognitive performance was enhanced when they received a stimulant, relative to placebo, even though the effects on their performance were small. Similarly, Looby and Earleywine (2011) found that individuals felt subjectively more stimulated when administered a stimulant, relative to when receiving a placebo, but did not perform differently on cognitive tests. Further research is needed to examine how expectancies might play a role in improving academic performance.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, some research supports that there might be a “placebo effect” associated with NPS (Ilieva et al, 2013; Looby & Earleywine, 2011). Ilieva, et al, (2013) observed that individuals believed that their cognitive performance was enhanced when they received a stimulant, relative to placebo, even though the effects on their performance were small.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for abuse and dependence of MPH is alarming considering the rise in the amount of children misdiagnosed and subsequently prescribed a stimulant medication for treatment [5,6]. Evidence suggests that MPH abuse has noticeably increased over the past several years [7,8]. In fact, of those persons aged 12 years and older, 4.2 million have used Ritalin or MPH recreationally at least once in their lifetime [9].…”
Section: Introductionmentioning
confidence: 99%